2013
DOI: 10.1080/09593330.2013.828094
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of an azo-dye on TiO2/activated carbon composite material

Abstract: A sequential adsorption/photocatalytic regeneration process to remove tartrazine, an azo-dye in aqueous solution, has been investigated. The aim ofthis work was to compare the effectiveness of an adsorbent/photocatalyst composite-TiO2 deposited onto activated carbon (AC) - and a simple mixture of powders of TiO2 and AC in same proportion. The composite was an innovative material as the photocatalyst, TiO2, was deposited on the porous surface ofa microporous-AC using metal-organic chemical vapour deposition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 47 publications
5
35
0
Order By: Relevance
“…Figure 8, the total degradation of [bmim]Cl increased until the optimum [photocatalyst] was achieved. Insufficient amount of photocatalyst supplied to the system will cause a blockage of the active site by [bmim]Cl, causing poor efficiency of the system [46]. As the dosage increased, the active sites available for the photodegradation process also increased, leading to a higher degradation rate.…”
Section: Effect Of Extrinsic Factor: Initial Ph Of the [Bmim]cl Solutionmentioning
confidence: 99%
“…Figure 8, the total degradation of [bmim]Cl increased until the optimum [photocatalyst] was achieved. Insufficient amount of photocatalyst supplied to the system will cause a blockage of the active site by [bmim]Cl, causing poor efficiency of the system [46]. As the dosage increased, the active sites available for the photodegradation process also increased, leading to a higher degradation rate.…”
Section: Effect Of Extrinsic Factor: Initial Ph Of the [Bmim]cl Solutionmentioning
confidence: 99%
“…Not only by its great specific surface area and low cost, but AC also give synergistic effect on photocatalysis via the strong adsorption properties which is also the controlling factor in photocatalysis 10,11 . From previous research, it is found that the combination of some photocatalyst with AC give synergistic effects 2,12 . There are several methods developed and reported by previous researches.…”
Section: Oohmentioning
confidence: 99%
“…Several techniques were developed including adsorption, oxidation and photooxidation method. Among some methods applicable for industrial scale, in recent years photocatalytic degradation of pollutant in aquatic system became the advance technique since it can reduce the cost the treatment due to its reusability [1][2][3] . The main factor in the system is highly active photocatalyst and one of the potential photocatalyts can be elected, ZnO materials have attracted much attention due to their excellent optical properties and facile synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate that a higher temperature and steam activation would enhance the adsorption capacity. The adsorption capacities of tartrazine over a variety of adsorbents (Klett et al 2014;Banerjee and Chattopadhyaya 2013;Wawrzkiewicz and Hubicki 2009;Mittal et al 2007;Dotto et al 2012;Ansari et al 2011;Monser and Adhoum 2009;Andriantsiferana et al 2014) are compared and reported in Table 6. …”
Section: Langmuir Isotherm Iodelmentioning
confidence: 99%